Consensus for the diagnosis, prognosis and treatment of feline mammary tumors - Cassali, Geovanni Dantas; de CAMPOS, Cecília Bonolo; Bertagnolli, Angélica Cavalheiro; Estrela-Lima, Alessandra; Lavalle, Gleidice Eunice; Damasceno, Karine Araújo; DE NARDI, Andrigo Barboza [UNESP]; Cogliati, Bruno; da COSTA, Fernanda Vieira Amorim; Sobral, Renata; Di Santis, Giovana Wingeter; Fernandes, Cristina Gevehr; et al. (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2019)
Mammary neoplasms are described as the third most common type of feline tumor, after haematopoietic and skin tumors, and present a challenge for clinicians because the prognosis for feline mammary tumors ranges from guarded to poor. Thus, it is necessary to define new therapeutic approaches and establish more in-depth knowledge about this disease in felines. The main aspects of the diagnosis, prognosis and treatment of feline mammary neoplasia were discussed, aiming to standardize the criteria and to serve as a guide for pathologists and veterinary clinicians.
Consenso para o diagnóstico, prognóstico e tratamento de tumores mamários em felinos
Keywords: Feline; Neoplasia; Pathology; Therapeutic